1990
DOI: 10.1128/iai.58.8.2613-2620.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Candida albicans mannan-induced, mannan-specific delayed hypersensitivity suppressor cells

Abstract: We have shown previously that CBA/J mice immunized with Candida albicans developed delayed hypersensitivity (DH) demonstrable with mannan (MAN) extracted from the same organism and that the intravenous (i.v.) injection of MAN prior to or during the immunization phase resulted in the suppression of the MAN-specific DH response. In this study, we demonstrate that MAN-induced suppression of DH is a T-lymphocyte-mediated phenomenon. Suppressor cells induced in vivo by the i.v. injection of MAN into naive mice 1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In addition, both specific and nonspecific modulation of immune responses have been reported as a consequence of C. albicans infection in mice. Garner et al (23) showed that mannan administered intravenously to naive mice induced a population of suppressor T lymphocytes that, when transferred to immunized mice, suppressed antigen-specific DTH responses. Ashman (24) suggested that active downregulation of protective immunity might occur in mice that are genetically susceptible to candidiasis and are characterized by high antibody levels and poor DTH responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both specific and nonspecific modulation of immune responses have been reported as a consequence of C. albicans infection in mice. Garner et al (23) showed that mannan administered intravenously to naive mice induced a population of suppressor T lymphocytes that, when transferred to immunized mice, suppressed antigen-specific DTH responses. Ashman (24) suggested that active downregulation of protective immunity might occur in mice that are genetically susceptible to candidiasis and are characterized by high antibody levels and poor DTH responses.…”
Section: Discussionmentioning
confidence: 99%
“…Values represent the means _+ SEM of three experiments. Specific antibody levels in uninfected mice were negligible or undetectable 23. Romani et al…”
mentioning
confidence: 99%
“…We reasoned that Candida-specific Ts cells would be a useful tool to study vaginal candidiasis under reduced Candida-specific CMI. The Ts cell approach was also relevant since Ts cells characterized both in patients with chronic mucocutaneous candidiasis (9, 35) and in murine models of cutaneous candidiasis (8,17) have been implicated in the development of Candida infections. Indeed, the presence of Candida-specific Ts cells at the time of vaginal inoculation effectively reduced the subsequent vaginal infection-derived systemic CMI.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the importance of CMI in gastrointestinal host resistance to C. albicans has been demonstrated in both humans (4,11,25) and animal models (2, 6-8, 12, 30). The use of murine models has allowed the identification of both lymphocyte populations that protect against Candida gastrointestinal infection (7,8,12) and those that down-regulate Candida-specific CMI, thus creating susceptibility to infection (3,17). Additionally, athymic (2, 6) and severe combined immunodeficient (Tand B-cell-deficient) (30) mice have been particularly useful for studying susceptibility to gastrointestinal candidiasis.…”
mentioning
confidence: 99%